Media Sosial dan Perubahan Budaya Masyarakat Perkotaan: Studi Kasus Kota Makassar - Dahlan, Mubarak (Rayhan Intermedia, 2025)
Social and cultural changes in urban communities have been influenced by the growth of social media. The purpose of this study is to see how social media affects the values, habits, and interaction patterns of people in urban environments. This study uses a qualitative approach to study the literature. Data were collected from various academic sources and related reports. The study shows that social media not only accelerates the exchange of information, but also has an impact on a person's lifestyle, cultural identity, and social relationships. Social media encourages modernization and globalization on the one hand, but also causes problems such as disinformation, individualism, and the destruction of local culture on the other. This study found that social media plays an important role in the socio-cultural changes of urban communities, so digital literacy is needed to maximize its benefits and reduce its negative effects.